A Comparison Study On Engine Oil Properties For Bi-Fuel Motorcycle - Zulkifli, Abdul Majid; Zulkefli, Yaacob; Mohd. Adnan, Yahya (2002)
All mechanical equipment must be lubricated in order to reduce friction and wear between the touching surfaces. For four-stroke motorcycle engine, the function of the engine oil play critical roles since the oil does not burn along with fuel in combustion chamber as two-stroke motorcycle engines. The oil will circulate around inside the engine and the quality of the oil will decreased time by time. In conjunction with that, the engine oil must be removed after certain running period or distance recommended by the engine manufactures. The use of natural gas as a vehicle fuel claimed to provide several benefits to engine components and effectively reduce maintenance requirements. It does not mix with or dilute the lubricating oil faster and will not cause deposits in combustion chambers as well as on spark plugs to the extend that the use of petrol does, thereby generally extending the engine oil, piston ring and spark plug. It is the intention of this paper to compare the effect of both physical and chemical properties of motorcycle engine oil used by MODENASS KRISS 110cc motorcycle engine after running 5000 km using natural gas and gasoline respectively.